Frontiers in free‐energy calculations of biological systems. (6th June 2013) - Chipot, Christophe
Abstract : Abstract : In a matter of three decades, free‐energy calculations have emerged as an indispensable tool to tackle deep biological questions that experiment alone has left unresolved. In spite of recent advances on the hardware front that have pushed back the limitations of brute‐force molecular dynamics simulations, opening the way to time and size scales hitherto never attained, they represent a cogent alternative to access with unparalleled accuracy the thermodynamics and possibly the kinetics that underlie the complex processes of the cell machinery. From a pragmatic perspective, the present review draws a picture of how the field has been shaped and invigorated by milestone developments, application, and sometimes rediscovery of foundational principles laid down years ago to reach new frontiers in the exploration of intricate biological phenomena. Through a series of illustrative examples, distinguishing between alchemical and geometrical transformations, it discusses how far free‐energy calculations have come, what are the current hurdles they have to overcome, and the challenges they are facing for tomorrow. WIREs Comput Mol Sci 2014, 4:71–89. doi: 10.1002/wcms.1157 This article is categorized under: Molecular and Statistical Mechanics > Free Energy Methods